2010
DOI: 10.1088/0004-6256/140/1/157
|View full text |Cite
|
Sign up to set email alerts
|

Variable Radio Sources in the Galactic Plane

Abstract: Using three epochs of VLA observations of the Galactic Plane in the first quadrant taken ∼ 15 years apart, we have conducted a search for a population of variable Galactic radio emitters in the flux density range 1-100 mJy at 6 cm. We find 39 variable sources in a total survey area of 23.2 deg 2 . Correcting for various selection effects and for the extragalactic variable population of active galactic nuclei, we conclude there are ∼ 1.6 Galactic sources deg −2 which vary by more than 50% on a time scale of yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 33 publications
3
69
0
Order By: Relevance
“…On the timescales of days to 15 years, Becker et al (2010) examined the variability of sources towards the Galactic plane in the flux density range 1−100 mJy. A surface density of 1.6 deg −2 variables was reported (8% of the sample).…”
Section: Comparison With Previous Variability Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…On the timescales of days to 15 years, Becker et al (2010) examined the variability of sources towards the Galactic plane in the flux density range 1−100 mJy. A surface density of 1.6 deg −2 variables was reported (8% of the sample).…”
Section: Comparison With Previous Variability Surveysmentioning
confidence: 99%
“…At ∼5 GHz, the deepest variability survey to date is that of Becker et al (2010), which probed a flux density greater than one mJy, an order of magnitude higher in flux than that of the Carilli et al (2003) survey. The Becker et al (2010) survey showed that the surface density of variable sources towards the Galactic Plane above one mJy is ∼1.6 deg −2 on timescales of days to years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that 2% of the sources within their sample were highly variable (defined as S ≥ 50%) and hence derived a rate of ρ = 18 deg −2 . Also in search of highly variable radio sources, Becker et al (2010) surveyed the Galactic plane and found ρ = 1.6 deg −2 above a sensitivity of 1 mJy at 4.8 GHz. At low Galactic latitude and sampling a multitude of timescales (days to years), Ofek et al (2011) used the VLA to study transient and variables in a field covering 2.66 deg 2 to a sensitivity limit of ∼100 μJy at 5 GHz.…”
Section: Gigahertz Surveysmentioning
confidence: 99%
“…While the possibility of some of these to be members of new types of Galactic sources cannot be ruled out, but Becker et al (2010) finds Galactic variable sources to have either a flat or inverted spectrum. Except one source, there is no other source whose spectral index is flatter than −0.3, and hence they are unlikely to be variable Galactic sources.…”
Section: Are the Small Diameter Sources Extragalactic ?mentioning
confidence: 99%